Interference and resource management in heterogeneous wireless networks - Li, Jiandong, 1962-; Sheng, Min; Wang, Xijun (Telecommunications engineer); Sun, Hongguang (Telecommunications engineer) (Artech House mobile communications series., 2018)
This authoritative resource offers a comprehensive overview of heterogeneous wireless networks, small cells, and device-to-device (D2D) communications. The book provides insight into network modeling and performance analysis of heterogeneous wireless networks. Interference management framework and design issues are covered as well as details about resource mobility, channel models, and typical and statistical interference modeling. This resource explains leveraging resource heterogeneity in interference mitigation and presents the challenges and feasible solutions for concurrent transmission.n nMoreover, complete coverage of interference alignment in MIMO heterogeneous networks for both downlink and uplink is presented. This book provides performance results for an ideal partially connected interference network as well as a practical heterogeneous network. Readers find practical guidance for LTE and LTE-Advanced as well as 5G in this resource. New techniques and designs for heterogeneous wireless networks are included.